(3eYLe eG GSJYLes - (3YHO Gddg Hf YHO GdYRjR Hf eMeO GdHcQj GdCfOdSj, CHh YHjO,J (B487 (3g` s
(3ChdgG (B:s
(3GdMGA hGdeje (B" (3MehI(B: s
(3BNQgG (B:s
(3fUjHjf (B: (3HaJM Chdg hcSQ KGfjI s
(3HgG fXGe GdJYbjHIs
(3ef HbjI MQa GdMGA h ,Gd (B: (3O , P, Q, R , W , X , c , d, e , fs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B75s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1737s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs